Paradoks Twiplomacy Donald Trump: Implikasinya Terhadap Kerentanan Keamanan Digital Amerika Serikat - Riska R (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The rise of social media has fundamentally shifted conventional diplomatic practices into the digital realm, giving birth to the phenomenon known as Twiplomacy. During his presidency (2017–2021), Donald Trump transformed platform X (formerly Twitter) into his primary diplomatic instrument through the @realDonaldTrump account, creating a major paradox: while Twiplomacy expanded the reach of real-time foreign policy communication, Trump's habitual oversharing and impulsive social media behavior systematically generated vulnerabilities in the United States' digital security posture. This article analyzes that paradox by identifying three primary risk dimensions arising from Trump's Twiplomacy activities: (1) leakage of classified state intelligence, (2) destabilization of global financial markets, and (3) escalation of diplomatic and military conflicts. The study employs a qualitative descriptive-analytical method grounded in a literature review approach, underpinned by securitization theory and digital security frameworks. The findings demonstrate that a head of state's digital communications when not balanced with rigorous cybersecurity protocols can transform from a soft power instrument into a genuine threat vector against national security stability.